Partnership for Change: Australia-China Joint Economic Report - China Center for International Economic Excha, East Asian Bureau of Economic Research (ANU Press, 2016)
The Australia-China Joint Economic Report is the first major independent joint study of the bilateral relationship and has the blessing of both national governments. The Report is an academic policy study by leading researchers in both Australia and China. It draws policy conclusions to guide the development of bilateral economic relations that include an Australia-China Comprehensive Strategic Partnership for Change, an Australia-China Commission, and an Australia-China Basic Treaty of Cooperation.